Application for mobile devices to increase efficiency of longan production - Somkeit Noamna (2018)
© 2017 American Scientific Publishers All rights reserved. This research aims to study and find ways to optimize the process of production of longan by agriculturists in Lamphun, Thailand. The focus is to increase the production by improving processes based on principles of industrial engineering. The in depth analysis of the longan trees cultivation process by using the diagram (Fish Bone Diagram) has determined what actions can be classified as NVA (no value added). The elimination and reduction of such processes when it comes to trimming branches and hedges was achieved through the use of information technology. The result of the experiment using an application that was developed and tested in pilot study with longan trees shows that it is possible to reduce processing time of longan trees trimming and increase longan production by up to 25 percent as shown in the results of the research (from 131.4 kg to 164.6 kg per tree on average).